Improving EFL Learners’ Speaking Ability through Storytelling Using Puppets - Wati, Laila; Fikni, Zahratul (VELES Voices of English Language Education Society, 2018)
This study was intended to describe how story-telling using puppets developed the speaking ability of the seventh graders of SMP Islam Terampil Nurul Mujahidin NW Pancor Kopong in the academic year 2014-2015. This research was a collaborative classroom action research following Kemmis and McTaggart’s cyclical process of planning, acting, observing, and reflecting. The data were collected by administering observation checklist, questionnaire, self-assessment, field notes, and recorder. The result of the analysis pointed out that storytelling using puppets was very helpful not only in improving the result but also the process of instructional process. This is proven by that all criteria of success set in this research were achieved. Therefore, English teachers are suggested to implement the technique and use the media in their English class particularly in speaking activities.